Photo-stimulated desorption from water and methane clusters on the surface of solid neon - Arakawa, Ichiro; Matsumoto, Daigo; Takekuma, Shinichi; Tamura, Reimi; Miura, Takashi (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Photo-stimulated desorption of ions from methane and water heterocluster on the surface of solid neon was studied. The desorption yields of the variety of photo-desorbed species showed strong dependence on the composition and the size of the mother cluster. It was found that the presence of a water molecule in the cluster significantly enhanced, or was almost essential for, the desorption of any species observed. Systematic investigation of the correlation between the cluster size and the desorption yield of each ion has revealed the mother cluster which yields the each desorbed ion.